Comment on: Family roles and the incidence of wasting in toddlers: A Study at Pulo Lor Health Center, Jombang Regency - Triwiyanto Triwiyanto; Sari Luthfiyah; bedjo utomo (International Journal of Advanced Health Science and Technology, 2025)
This letter to the editor addresses the significant findings and limitations of the study on the impact of family roles on toddler nutrition. While the research reveals a crucial link between family dynamics and the incidence of wasting, it is constrained by its cross-sectional design and dependence on self-reported data, potentially obscuring causal relationships. The letter advocates for the inclusion of longitudinal studies and qualitative methods to better understand family influences on nutritional outcomes. It also emphasizes the importance of culturally informed approaches and the alignment of research with public health policies to develop effective interventions for improving toddler nutrition across diverse communities.